Strategy for Winning Science Elections After the Covid-19 Pandemic - Kelik Endro Suryono; Aida Dewi; Vicki Dwi Purnomo (International Journal of Integrative Sciences, 2023)
Strategies for the Dikulon Progo Post-Pandemic Election in 2024. This research uses a qualitative method approach. Sources of research data include primary and secondary data sources. Data collection tools and techniques use interviews and documentation. Test the validity of the data in this study using the source triangulation technique. The research data that has been collected is then analyzed including data collection; presentation of data; and conclusion or verification. The results showed that the strategy for winning elections was by formulating work programs, mass mapping, branding and positioning , political marketing strategies , political communications, political campaigns using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), as well as approaches to farmers, community leaders and religious leaders. Having a solid team and receiving support from community organizations in Kulon Progo Regency in the form of materials and mass